Analysis Of The Usefulness Of E-Commerce Payment Features In The Potential Shopping Ability Of Society - Ong, Danny; Imron, Imron; Sinta Nurhayati, M.; Rosano , Andi (CV. Publikasi Indonesia, 2025)
Payment is a final process which is a sign of the agreement that a transaction has been successfully carried out and there is an agreement. In this study related to the discussion of payment variation mechanisms will be discussed on functions in e-commerce. Payment features are many features and are highly expected by consumers because the choice of payment features will provide consumers with many options when completing a transaction coupled with the potential for cash banks and installment mechanisms provided by the platform. Payment variations are a mechanism that must be implemented by e-commerce in collaboration with payment service providers. From research conducted using the SWOT and Balance Scorecard methods, it can be found that with variations in payment, especially for bank installment mechanisms, it automatically increases people's spending ability for transactions with a large scope where e-commerce transactions tend to be mostly filled with transactions. retail with a nominal value that is not so large. Purchasing power and public spending potential with this variation also indirectly increases where the resulting research is at point 4 to 5 of the survey conducted. So that from all this it can be concluded that the more a variety of payments provided by the platform, the greater the potential to increase the ability and attractiveness of the public to make purchases because each community has different means of payment, indeed the potential is the same but there is a tendency for people in some small areas do not have access to a variety of banking services so that the presence of variety and the provision of these services will indirectly increase the purchasing potential of the public